Effects of occupational noise on quality of life - Otoghile, Bright; Onakoya, Paul A.; Otoghile, Confidence C. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Noise is an unwanted sound which could possibly adversely impact an individual’s quality of life. The issue of occupational noise is of public health importance. Excessive noise can potentially affect the quality of life. The objective of the study was to evaluate the effects of occupational noise exposure on quality of life. Methods: This was a prospective community based study involving sawmill workers in Ile-Ife. Library and administrative staff of Obafemi Awolowo University, Ile-Ife were used as control. The quality of life of all participants was evaluated with World Health Organization Quality of Life bref questionnaire and a designed noise exposure evaluation questionnaire. Results: A total of 420 subjects were recruited for the study and similar number for control. There was a negative correlation between occupational noise and the physical and psychological domains of quality of life. Conclusions: Occupational noise level is associated with a reduction in the overall, physical and psychological components of the quality of life.